Comprehensive molecular characterisation of endemic and sporadic methicillin resistant Staphylococcus aureus recovered in Irish hospitals - Kinnevey, Peter (Trinity College (Dublin, Ireland). School of Dental Science, 2011)
Methicillin-resistant Staphylococcus aureus (MRSA) is a prevalent pathogen responsible for hospital- and community-acquired infections worldwide. Molecular typing of Irish MRSA isolates has revealed that different MRSA strains have predominated at different time periods and currently ST22-MRSA-IV predominate in Irish hospitals. Isolates of this highly-clonal strain are difficult to discriminate effectively with currently used typing methods including multilocus-sequence typing (MLST), staphylococcal cassette chromosome mec (SCCmec) typing, spa typing and pulsed-field gel electrophoresis (PFGE). In the present study, the ability of combining sequencing of the SCCmec encoded direct repeat unit (dru) with spa and PFGE typing to enhance discrimination of ST22-MRSA-IV isolates (n = 168) recovered in one Irish hospital during 2007 and 2008 was investigated. The combination of all three typing methods yielded the highest number of type combinations (65) and the highest discriminatory power (Simpson's index of diversity of 96.53) compared to any of the individual typing methods used alone or in pairwise combinations. Analysis of epidemiological information for a subset of ST22-MRSA-IV isolates validated the relationships inferred using combined spa, dru and PFGE typing data. The combination of all three typing methods significantly enhanced discrimination of the ST22-MRSA-1V isolates. Such an approach may also be beneficial for typing isolates of other highly-clonal MRSA strains.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin